Combined Impact of Network Reconfiguration and Volt-VAR Control Devices on Energy Savings in the Presence of Distributed Generation - Pamshetti V.B.; Singh S.; Singh S.P. (My University, 2025)
Reduction of energy consumption and energy losses is a major concern of the distribution network operator in the present scenario. Traditionally, on-load tap changers, a shunt capacitor bank, and a voltage regulator have been employed as volt-var control (VVC) devices for savings in energy consumption and losses. In this paper, an efficient and optimally coordinated operation of traditional VVC devices, a distribution network reconfiguration (DNR), and a photovoltaic smart inverter (PVSI) for energy savings has been proposed. In order to achieve the optimal solution, a modified binary gray wolf optimization (MBGWO) algorithm has been proposed. Besides, the proposed method in association with PVSI droop control has been employed to control the voltage violations during cloudy day condition. Furthermore, the proposed method has been employed for service restoration considering voltage regulation and peak demand reduction under faulty condition. For validation, the performance of the proposed algorithm has been tested on balanced as well as unbalanced distribution systems. The test results demonstrate the significance of the DNR associated with VVC devices and PVSI for energy savings under different load models. Outcome of the proposed algorithm has been compared with other existing metaheuristic algorithms and test results demonstrate the benefit of the proposed method. © 2007-2012 IEEE.